If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3 + 2x = 3(2x + 4) + -5(x + -2) Reorder the terms: 3 + 2x = 3(4 + 2x) + -5(x + -2) 3 + 2x = (4 * 3 + 2x * 3) + -5(x + -2) 3 + 2x = (12 + 6x) + -5(x + -2) Reorder the terms: 3 + 2x = 12 + 6x + -5(-2 + x) 3 + 2x = 12 + 6x + (-2 * -5 + x * -5) 3 + 2x = 12 + 6x + (10 + -5x) Reorder the terms: 3 + 2x = 12 + 10 + 6x + -5x Combine like terms: 12 + 10 = 22 3 + 2x = 22 + 6x + -5x Combine like terms: 6x + -5x = 1x 3 + 2x = 22 + 1x Solving 3 + 2x = 22 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 3 + 2x + -1x = 22 + 1x + -1x Combine like terms: 2x + -1x = 1x 3 + 1x = 22 + 1x + -1x Combine like terms: 1x + -1x = 0 3 + 1x = 22 + 0 3 + 1x = 22 Add '-3' to each side of the equation. 3 + -3 + 1x = 22 + -3 Combine like terms: 3 + -3 = 0 0 + 1x = 22 + -3 1x = 22 + -3 Combine like terms: 22 + -3 = 19 1x = 19 Divide each side by '1'. x = 19 Simplifying x = 19
| 3x-(8-x)=5(3-x)+4 | | -7+2x=-25-x | | x-(8-x)=5(3-x)+4 | | 10+12=-34+x | | 2x+10-7x=3(x-5)+1 | | 3*(x+2)=3x+32 | | 7(2x+1)=5x+16 | | 9x+8+2x+6=7x+2 | | 8x-5x=8 | | 10p-4=86 | | -7+8x-19=15+3(x-17) | | 5/m=8/6 | | 2[t+6]-1=9 | | 3/n=10/7 | | x+8(12-x)=7x-(5x-42) | | 6/a=5/7 | | -16=-4[v+3] | | 1/2-3x=-1/2 | | -4+5x=36 | | x+8(12-x)=7x(5x-42) | | -8x-5x-96=60 | | 8/3=n/4 | | x-7x-61=23 | | 7=2[r+6]-5 | | r(x)=x(13-0.04x) | | -15=10+5v | | -2x-10+3x=9 | | 62=-7v-1 | | 2[w+2]=10 | | 9x^4/3x^3 | | 3a-1/6-1-4a/12=1 | | 37=7+6x |